2015
DOI: 10.1111/jnc.13125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the beta‐adrenergic receptor antagonist Propranolol on dyskinesia and L‐DOPA‐induced striatal DA efflux in the hemi‐parkinsonian rat

Abstract: Dopamine (DA) replacement therapy with L-DOPA continues to be the primary treatment of Parkinson's disease; however, long-term therapy is accompanied by L-DOPA-induced dyskinesias (LID). Several experimental and clinical studies have established that Propranolol, a β-adrenergic receptor antagonist, reduces LID without affecting L-DOPA's efficacy. However, the exact mechanisms underlying these effects remain to be elucidated. The aim of the current study was to evaluate the anti-dyskinetic profile of Propranolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…Other noradrenergic drugs, as the badrenergic receptor antagonist propranolol and the a 2 -receptor agonist clonidine also showed antidyskinetic effects in MPTPtreated monkeys, at the cost of reducing the antiparkinsonian efficacy (Gomez-Mancilla and Bédard, 1993). Experiments performed in 6-OHDA lesioned rats support the prodyskinetic action of the a 2 -antagonist atipamezole and the antidyskinetic effect of propranonol, clonidine, or idazoxan, which did not worsen motor performance (Dekundy et al, 2007;Gerlach et al, 2013;Bhide et al, 2015;Ostock et al, 2015). These findings suggest that the limited though beneficial effect of clonidine on LID is probably indirect due to the stimulation of somatodendritic a 2 -receptors, which inhibit noradrenergic neuronal activity and NA release.…”
Section: L-dopa and The Noradrenergic Systemmentioning
confidence: 90%
“…Other noradrenergic drugs, as the badrenergic receptor antagonist propranolol and the a 2 -receptor agonist clonidine also showed antidyskinetic effects in MPTPtreated monkeys, at the cost of reducing the antiparkinsonian efficacy (Gomez-Mancilla and Bédard, 1993). Experiments performed in 6-OHDA lesioned rats support the prodyskinetic action of the a 2 -antagonist atipamezole and the antidyskinetic effect of propranonol, clonidine, or idazoxan, which did not worsen motor performance (Dekundy et al, 2007;Gerlach et al, 2013;Bhide et al, 2015;Ostock et al, 2015). These findings suggest that the limited though beneficial effect of clonidine on LID is probably indirect due to the stimulation of somatodendritic a 2 -receptors, which inhibit noradrenergic neuronal activity and NA release.…”
Section: L-dopa and The Noradrenergic Systemmentioning
confidence: 90%
“…However, using physiological recordings and dendritic reconstruction techniques, recent studies have revealed that iSPNs undergo profound structural-functional adaptations in LID models (38,45). Moreover, several studies have reported D2 agonist-induced dyskinesias in experimental models of PD (46)(47)(48). These considerations highlight the importance of testing the causality of dSPN and iSPN activity in the genesis of parkinsonian hypokinesia and dyskinesia.…”
Section: Discussionmentioning
confidence: 99%
“…5754 Propranolol, a beta-adrenergic receptor antagonist, has been 5755 regularly suggested to exhibit some anti-dyskinetic potential, 5756 without affecting L-DOPA's efficacy. Propranolol, in a dose-5757 dependent manner, reduced LID, without affecting motor perfor-5758 mance in the AIM rat model of LID (Bhide et al, 2015) but failed to 5759 alter dyskinesia produced by the D1 receptor agonist SKF81297 or 5760 the D2 receptor agonist Quinpirole. These findings suggested a pre-5761 synaptic mechanism for Propranolol's anti-dyskinetic effects, 5762 possibly through modulating L-DOPA-mediated DA efflux, as 5763 unravelled demonstration of propranolol-mediated reduction in L-5764 DOPA-induced DA efflux (Bhide et al, 2015).…”
mentioning
confidence: 96%
“…Propranolol, in a dose-5757 dependent manner, reduced LID, without affecting motor perfor-5758 mance in the AIM rat model of LID (Bhide et al, 2015) but failed to 5759 alter dyskinesia produced by the D1 receptor agonist SKF81297 or 5760 the D2 receptor agonist Quinpirole. These findings suggested a pre-5761 synaptic mechanism for Propranolol's anti-dyskinetic effects, 5762 possibly through modulating L-DOPA-mediated DA efflux, as 5763 unravelled demonstration of propranolol-mediated reduction in L-5764 DOPA-induced DA efflux (Bhide et al, 2015). Therefore, Propra-5765 nolol's anti-dyskinetic properties appear to be mediated via 5766 attenuation of L-DOPA-induced extraphysiological efflux of DA, 5767 comparably to 5-HT 1A/1B agonists.…”
mentioning
confidence: 96%